Comparison of Neutrophil to Lymphocytes (N/L) Ratio in Pregnancy and Lactation of Thin-Tail Sheep - Sulistyowati Ari; Astuti Pudji; Mona Airin Claude; Sarmin; Adianto Nur (BIO Web of Conferences, 2022)
Thin-tailed sheep are the most widely kept sheep species in Indonesia. The neutrophils and lymphocytes (N/L) ratio can be a stress indicator for sheep. Stress conditions can cause animals to experience impaired growth, productivity, and behavioral changes. However, the study of thr N/L ratio during pregnancy and lactation in thin tailed sheep is still lacking and variations in physiological status such as pregnancy and lactation condition can cause differences in the N/L ratio. This study was conducted to determine the stress level on the physiological status of pregnant and lactating thin tailed sheep by looking at the difference in the N/L ratio. The blood samples used were seven pregnant sheep and five lactating sheep rearing in El Farm Ternak Domba Kambing dan Pendopo Sawah Kunden, Berbah, Sleman, Yogyakarta. The data obtained were analyzed using the Independent T-test method with the help of SPSS software version 16. The result of statistical analysis showed that the ratio N/L of pregnancy and lactation in thin tailed sheep was no significant difference (P>0.05). However, the average N/L ratio in pregnant conditions was higher, it was 0.61 ± 0.95, while in lactation conditions, it was 0.23 ± 0.30. The conclusion obtained from this study showed that the difference in the physiological status of pregnancy and lactation had no significant effect on the N/L ratio in ewes and the two physiological conditions of the studied sheep were still within normal limits.